2014
DOI: 10.1103/physrevx.4.041015
|View full text |Cite
|
Sign up to set email alerts
|

Odor Landscapes in Turbulent Environments

Abstract: International audienceThe olfactory system of male moths is exquisitely sensitive to pheromones emitted by females and transported in the environment by atmospheric turbulence. Moths respond to minute amounts of pheromones, and their behavior is sensitive to the fine-scale structure of turbulent plumes where pheromone concentration is detectible. The signal of pheromone whiffs is qualitatively known to be intermittent, yet quantitative characterization of its statistical properties is lacking. This challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
285
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(293 citation statements)
references
References 57 publications
5
285
2
1
Order By: Relevance
“…the physical and chemical environment that marine microbes experience in the ocean (17), the flow environment that influences search decisions of planktonic predators (33), and the physical structure and chemical composition of the odor plumes to which moths and other olfactory searchers respond (5,10,11,34,35). These studies notwithstanding, we have little quantitative information about the structure and spatiotemporal dynamics of the environments in which most organisms search, largely because of the difficulty of quantifying spatially and temporally varying cues in natural settings.…”
Section: The Evolution Of Search Strategiesmentioning
confidence: 93%
See 3 more Smart Citations
“…the physical and chemical environment that marine microbes experience in the ocean (17), the flow environment that influences search decisions of planktonic predators (33), and the physical structure and chemical composition of the odor plumes to which moths and other olfactory searchers respond (5,10,11,34,35). These studies notwithstanding, we have little quantitative information about the structure and spatiotemporal dynamics of the environments in which most organisms search, largely because of the difficulty of quantifying spatially and temporally varying cues in natural settings.…”
Section: The Evolution Of Search Strategiesmentioning
confidence: 93%
“…In wind-tunnel experiments with moths, odors that are pulsed in this natural frequency range cause strong firing responses in central olfactory neurons, and elicit stereotyped search behavior, whereas odors outside this range elicit weak responses at both the neural and behavioral levels. At greater distances from an odor source, pulses of odor are far more intermittent, yet moths and other insects are still able to distinguish relevant olfactory cues from noise and to use these cues to navigate (5). The neural mechanisms that underpin this long-range response to odors are still poorly understood, but quantitative characterization of odor landscapes has provided crucial clues (5,11).…”
Section: Boxmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we leverage the advantages of controlled laboratory conditions to demonstrate that mice can make use of airborne odor cues to locate a source. The complexity of airborne odor plumes is well-documented [12], creating a rich and dynamic stimulus for odor-based navigation. Work using simplified odor cues has suggested that rodents may be able to measure odor gradients with just one or two sniffs [13,14].…”
Section: Introductionmentioning
confidence: 99%